The plastic arts as object of the investigation the Venezuelan University, transversality between science- technology (Revista Electrónica REDINE, 2018)
The visual arts beyond the creative act, which seems to culminate in the work of art, is concentration of the society where it is inserted, which should be considered as a starting point for research from universities. However, it is hard to find grants for such research, since the impact of resources for the financing of this work has investigated the areas of natural science and technology was considered as guarantors of better products and more social benefits. Thus the arts which make up part of the social sciences are confronted with the inconvenience of having to be relegated. Art as a cultural fact should be brought to light with all its properties, benefits and products and this would only be through research carried conveniently considering that the human material for research is in the decent-researchers in our universities.
Keywords: art; social sciences; technology; university research